Inhibice systému renin-angiotenzin-aldosteron u srdečního selhání aneb od obecného souhlasu (CONSENSUS) po vzorec myšlení (PARADIGM-HF) - Vítovec, Jiří; Špinar, Jindřich; Špinarová, Lenka (Vnitrni lekarstvi, 2015)
An historical survey is presented of mortality trials on angiotensin-aldosteron system inhibition in patients with chronic heart failure. From the CONSENSUS trial up to the PARADIGM-HF trial, ACE inhibitors/angiotensin II receptor antagonists (AT1-blockers, ARBs, sartans), along with mineralocorticoid receptor blockers, have been the gold standard of treatment. Both direct renin blocker aliskiren and dual blocker enalapril + neprilysin proved ineffective; on the other hand, the new dual inhibitor valsartan + neprilysin LCZ 696 is a new and promising therapeutic agent for future treatment of chronic heart failure.
Keywords: inhibitory ACE; Consensus; Heart Failure; Renin-Angiotensin System; Humans; lidé; srdeční selhání; renin-angiotensin systém; Angiotensin-Converting Enzyme Inhibitors; Angiotensin Receptor Antagonists; antagonisté receptorů pro angiotenzin; konsensus